Anesthetic management of the SRS (TM) endoscopic stapling system for gastro-esophageal reflux disease - Topuz, Ufuk; Umutoglu, Tarik; Bakan, Mefkur; Ozturk, Erdogan (My University, 2013)
The SRS (TM) Endoscopic Stapling System (Medigus, Tel Aviv, Israel) is a new tool capable of creating a totally endoscopic fundoplication, combined with an endoscope, endoscopic ultrasound and a surgical stapler. SRS (TM) endoscopic stapling for gastro-esophageal reflux disease is a minimally invasive, outpatient procedure, which requires general anesthesia with positive-pressure ventilation. Keeping the patient on positive end-expiratory pressure (PEEP) may minimize the pressure gradient between the esophagus and the mediastinum, as well as help to prevent air from leaking around the screws and causing pneumomediastinum. In addition, in patients with hiatal hernia, higher PEEP levels may be required to increase intra-thoracic pressure and to force the stomach to slide into the abdomen for ease of endoscopy. We advise smoother emergence from anesthesia, taking precautions for retching, postoperative nausea and vomiting (PONV), while coughing and gagging during extubation and PONV may affect the success of the procedure. Total intravenous anesthesia with propofol and remifentanil seems to be a good choice for these reasons. (C) 2013 Baishideng. All rights reserved.
Keywords: Endoscopy